Evaluating the efficacy of placental-derived allograft in managing non-healing pressure ulcers (International Journal of Tissue Repair, 2025)
Background: Chronic wounds such as pressure ulcers (PUs) cause physical, emotional and financial strain on patients. Amniotic membranes have been demonstrated in previous studies to aid wound closure.Methods: This study aims to examine the efficacy of cellular, acellular, and matrix-like products (CAMPs) in achieving complete closure of PUs that were not responsive to standard of care (SOC) treatment.Results: Overall, 25 subjects with 37 pressure ulcers that had failed to heal with 6 weeks of SOC were treated with three-layer placental derived allograft (TLPA) for up to 16 weeks. Mean age was 69.3 years, 16 patients were female, and 9 were male. At baseline prior to intervention, mean wound size was 44.9cm2 (SD 103.5) and three (8.1%) PUs achieved 40% or greater percent area reduction (PAR). At the end of TLPA treatment, 33 (89.2%) of PUs had a PAR of 40% or greater.Conclusion: TLPA treatment was shown to achieve 40% or more wound area reduction in this cohort of 25 subjects with 37 PUs that had not responded to SPC. The observed rate of improvement supports further investigation of TLPA in prospective controlled studies to validate efficacy, assess time to closure, and determine cost-effectiveness for PUs.